THE EFFECT OF RICE STRAW COMPOST TYPES STIMULATED WITH TRICHODERMA AND MANURE ON AVAILABLE-P AND GROWTH OF CORN PLANT (Zea mays L.) ON ULTISOLS - SUTRISNO SUTRISNO; Sutarman Gafur; Ismahan Umran (Jurnal Sains Pertanian Equator, 2018)
ABSTRACTRice straw is one of agricultural waste that has the potential to add nutrients in the soil. to accelerate the composting process is treated the role of microorganisms such as trichoderma sp and manure. the aim of this research is to know the effect of giving straw compost types with Trichoderma Stimulator and manure to P-available and growth of corn plant (Zea mays L.) on Ultisol soil. This research was conducted from February 25, 2017 to August 13, 2017. Complete Random Design (RAL) design consists of 4 treatments with 5 replications, 2 sets of plants so that the number of plants as many as 40 plants, this research was conducted in the experimental garden of Mount Meliau Garden Four Afdeling Meliau Sub-district, Sanggau District. the treatment is coded K0 (without compost), K1 (compost (straw + tricoderma)), K2 (compost (straw + tricoderma + manure)), K3 (compost (straw + manure)). The results showed that the effect of several straw compost with Trichoderma Stimulator and manure differed significantly on the growth of corn plant (Zea mays L.), but had no significant effect on the availability of P-soil in maize. Keywords: Ultisol, Rice Straw Compost, Trichoderma sp., Corn